Transformasi Destinasi Kuliner Lokal ke Arah Smart Tourism: Pendekatan Innovism dan Pemasaran Kewirausahaan - Yuliani Istiqomah; Dina Yulia Wijaya (Cattleya Darmaya Fortuna, 2025)
This study explores the transformation of Cibugel District into a smart culinary tourism destination through the integration of innovism and entrepreneurial marketing approaches. Utilizing a qualitative exploratory method, data were collected through in-depth interviews, participant observations, and documentation involving local culinary SMEs, village officials, student communities, and consumers. The findings reveal that while there is strong entrepreneurial orientation among local actors, the implementation of digital marketing and innovation remains limited. Innovism defined as locally-driven, socially collaborative, and technology-enhanced innovation emerged as a potential driver for reconfiguring culinary tourism into participatory and experience-based attractions. Meanwhile, entrepreneurial marketing provides a strategic framework for promoting local culinary products in competitive and sustainable ways. The synergy of these approaches is key to redefining rural culinary destinations not only as places to eat but also as spaces for cultural interaction, storytelling, and digital engagement. The study recommends contextualized policy support, continuous digital training, and community-based innovation to sustain the transformation process. This research contributes theoretically to the development of village-based smart culinary tourism and offers practical implications for regional tourism planning and local economic empowerment.